Self-repairing ceramic paint, coating, preparation method and application
By applying self-repair ceramic coating on the surface of the ammunition, and using the combination of microcapsules and silicone carbon ceramic layers, the problem of scratches and corrosion during transportation is solved, and the dual functions of self-repair and corrosion resistance are realized, improving the service safety of ammunition.
Patent Information
- Application Number
- CN202510052978.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
Ammunition is prone to scratches and scratches during transportation, and is prone to corrosion in high humidity, high temperature and high salt spray environments, affecting service safety.
Self-healing ceramic coating is used, which contains polydimethylsiloxane, xylene and microcapsules. The core of the microcapsules is epoxy resin and the wall of the capsule is polyurea formaldehyde. It forms a silicone carbon ceramic layer through laser cracking, which has the ability to self-heal.
The self-healing ceramic coating formed has self-healing ability for scratches, enhances the corrosion resistance of the surface of the bullet, improves the service safety of the ammunition, and has a long-term protective effect.
Smart Images

Figure BDA0005240858020000051 
Figure HDA0005240858040000011 
Figure HDA0005240858040000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of corrosion-resistant coatings, and in particular relates to a self-repairing ceramic coating, a coating, a preparation method and an application thereof. Background Art
[0002] When the ammunition is hit or clamped by the ammunition belt during transportation, scratches and other damages will appear on the surface of the projectile, which will damage the metal matrix. These damaged parts are very susceptible to corrosion in the atmospheric environment or in high humidity, high temperature, and high salt fog environments. The occurrence of corrosion will greatly affect the service safety of the ammunition. To address this problem, it is usually necessary to repair and strengthen the corroded parts, such as stripping the paint and then repainting, etc. This method has a long cycle, complex operation, and high cost.
[0003] The surface strengthening treatment of the projectile can enhance the scratch resistance, wear resistance and corrosion resistance of the projectile to a certain extent, such as applying grease, paint, and forming an oxide film on the outer surface of the projectile. However, the above methods still cannot avoid scratches on the projectile surface, and scratches are still easy to corrode, affecting the service safety of the ammunition. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a self-repairing ceramic coating, coating, preparation method and application. The self-repairing ceramic coating of the present invention is applied to the surface of the projectile, and the obtained self-repairing ceramic coating has the ability to self-repair scratches, the corrosion resistance of the projectile surface is enhanced, and the service safety of the ammunition is improved.
[0005] The present invention provides a self-repairing ceramic coating, comprising polydimethylsiloxane, xylene and microcapsules;
[0006] The capsule core of the microcapsule is epoxy resin, and the capsule wall is polyurea formaldehyde; the mass content of the microcapsules in the self-repairing ceramic coating is 10-20%;
[0007] The mass ratio of the polydimethylsiloxane to xylene is 2-4:1-3.
[0008] Preferably, the average particle size of the microcapsules is 90 to 140 μm, and the thickness of the capsule wall is 30 to 50 μm.
[0009] Preferably, the epoxy resin includes epoxy resin 711 and bisphenol A epoxy resin E-51, and the volume ratio of the epoxy resin 711 to the bisphenol A epoxy resin E-51 is 1:4-6.
[0010] Preferably, the microcapsules are prepared by an in-situ polymerization method, which comprises the following steps:
[0011] Mixing urea, ammonium chloride, resorcinol and water to obtain a mixed solution;
[0012] The epoxy resin is added dropwise to the mixed solution, the pH value is adjusted to 3.3-3.7, and the mixed solution is mixed with a formaldehyde aqueous solution to carry out an in-situ polymerization reaction to obtain microcapsules.
[0013] Preferably, the in-situ polymerization reaction is carried out at a temperature of 50 to 60° C. and for a time of 4 to 6 hours.
[0014] The present invention also provides a method for preparing a self-repairing ceramic coating, comprising the following preparation method:
[0015] The self-repairing ceramic coating described in the above technical solution is applied to a metal surface, and the obtained prefabricated coating is laser cracked under a protective atmosphere to crack the polydimethylsiloxane in the coating to form silicon-oxygen-carbon ceramics, thereby obtaining a self-repairing ceramic coating.
[0016] Preferably, the protective atmosphere gas is argon, and the flow rate of the argon is 350-500 mL / min.
[0017] Preferably, the parameters of the laser cracking include: fiber pulse laser, wavelength of 1064nm, line width of 10-15mm, power of 100-400W, scanning speed of 10-15mm / s, scanning times of 3-4 times, overlap rate of 5%, and S-shaped scanning path.
[0018] The present invention also provides a self-repairing ceramic coating obtained by the preparation method described in the above technical solution, comprising a silicon-oxygen-carbon ceramic layer and microcapsules dispersed in the silicon-oxygen-carbon ceramic layer.
[0019] The present invention also provides the use of the self-repairing ceramic paint or self-repairing ceramic coating described in the above technical solution in the clamped annular surface of the projectile.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention provides a self-repairing ceramic coating, comprising polydimethylsiloxane, xylene and microcapsules; the capsule core of the microcapsules is epoxy resin, and the capsule wall is polyurea formaldehyde; the mass content of the microcapsules in the self-repairing ceramic coating is 10-20%; the mass ratio of the polydimethylsiloxane to xylene is 2-4:1-3.
[0022] The present invention innovatively combines microcapsules with a precursor (polydimethylsiloxane) for preparing a silicon-oxygen-carbon ceramic layer. The self-healing ceramic coating of the present invention is applied to the surface of the projectile to obtain a self-healing ceramic coating. The silicon-oxygen-carbon ceramic layer has an excellent supporting effect, which can protect the microcapsules therein from being crushed or scratched by a slight external force, and the ceramic layer itself has a good isolation and protection effect, which can protect the surface of the projectile. When the surface of the projectile is scratched, the microcapsules rupture, and the anti-corrosion and corrosion-resistant liquid (epoxy resin) in the microcapsules flows out, forming an emergency protective isolation layer at the scratched part, and the corrosion resistance of the projectile surface is enhanced. The coating formed by the self-healing ceramic coating of the present invention has the ability to self-repair scratches and has a long-lasting protective effect, which improves the service safety of ammunition.
[0023] The present invention also provides a method for preparing a self-healing ceramic coating. The present invention innovatively combines self-healing micro units (microcapsules) with a ceramic layer, and adopts a method of laser cracking a prefabricated precursor to solve the problem that the self-healing microcapsules cannot be "embedded" in the ceramic layer. The microcapsules have the dual functions of corrosion resistance and wear resistance, as well as self-repair after damage to provide secondary corrosion protection. The coating of the present invention will not cause the problem of safety degradation to ammunition. The preparation method of the coating of the present invention is simple to operate, low in cost, high in output, and suitable for industrial production.
[0024] The present invention also provides the application of the self-repairing ceramic coating in the clamped annular surface of the projectile. The self-repairing ceramic coating can be applied only to the clamped portion of the projectile, thereby saving costs and improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 Schematic diagram of the coating ring surface of the corrosion-resistant strengthening self-repairing coating on the clamped ring surface of the projectile in the embodiment;
[0027] Figure 2 This is a process flow chart of preparing polyurea formaldehyde coated epoxy resin core microcapsules by in-situ polymerization in the embodiment;
[0028] Figure 3 This is a process flow chart of preparing SiOC ceramic coating by laser pyrolysis microcapsule filling system in the embodiment;
[0029] Figure 4The scanning electron microscope images of the polyurea formaldehyde coated epoxy resin core microcapsules prepared by in-situ polymerization in the examples, wherein (a) is the overall image and (b) is the capsule shell of the broken capsule;
[0030] Figure 5 This is a scanning electron microscope image of a microcapsule that was broken after the elastomer ceramic layer was scratched;
[0031] Figure 6 This is an electron microscope image of two microcapsules that cracked after the projectile ceramic layer was scratched;
[0032] Figure 7 This is an electron microscope image of the microcapsule-filled ceramic layer (microcapsule rupture) prepared by the laser cracking process of Comparative Example 1. DETAILED DESCRIPTION
[0033] The present invention provides a self-repairing ceramic coating, comprising polydimethylsiloxane, xylene and microcapsules;
[0034] The capsule core of the microcapsule is epoxy resin, and the capsule wall is polyurea formaldehyde; the mass content of the microcapsules in the self-repairing ceramic coating is 10-20%;
[0035] The mass ratio of the polydimethylsiloxane to xylene is 2-4:1-3.
[0036] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.
[0037] In the present invention, the mass ratio of the polydimethylsiloxane to xylene is 2-4:1-3, and specifically may be 3:2.
[0038] In the present invention, the mass content of microcapsules in the self-repairing ceramic coating is 10-20%, specifically 13-15%.
[0039] In the present invention, the average particle size of the microcapsules is preferably 90 to 140 μm, and the thickness of the capsule wall is preferably 30 to 50 μm.
[0040] In the present invention, the epoxy resin preferably includes epoxy resin 711 and bisphenol A epoxy resin E-51, and the volume ratio of the epoxy resin 711 to the bisphenol A epoxy resin E-51 is preferably 1:4-6, specifically 1:5.
[0041] In the present invention, the microcapsules are preferably prepared by in-situ polymerization using urea and formaldehyde as capsule wall materials and epoxy resin as capsule core; the in-situ polymerization method preferably includes the following steps:
[0042] Mixing urea, ammonium chloride, resorcinol and water to obtain a mixed solution;
[0043] The epoxy resin is added dropwise to the mixed solution, the pH value is adjusted to 3.3-3.7, and the mixed solution is mixed with a formaldehyde aqueous solution to carry out an in-situ polymerization reaction to obtain microcapsules.
[0044] In the present invention, the usage ratio of urea, ammonium chloride, resorcinol and water is preferably 5g:0.5g:0.5g:200mL.
[0045] In the present invention, the volume ratio of the epoxy resin to the mixed liquid is preferably 1525:200.
[0046] In the present invention, the pH regulator is preferably hydrochloric acid, and the present invention has no special requirements on the concentration of the hydrochloric acid.
[0047] In the present invention, the concentration of the formaldehyde aqueous solution is preferably 37 wt %, and the mass ratio of formaldehyde in the urea and formaldehyde aqueous solution is preferably 5:4.5-5.5, specifically 5:4.7.
[0048] In the present invention, the temperature of the in-situ polymerization reaction is preferably 50-60° C., and the time is preferably 4-6 hours, specifically 5 hours.
[0049] In the present invention, after the in-situ polymerization reaction, the following steps are preferably performed: solid-liquid separation, extraction, washing and drying of the reaction solution obtained by the in-situ polymerization reaction; the solid-liquid separation is preferably suction filtration, the extraction solvent is preferably ethyl acetate, and the washing is preferably water washing.
[0050] The in-situ polymerization method can be summarized into three stages: "liquid phase separation-wetting and wrapping-film layer solidification". The liquid phase separation process is the emulsification and dispersion of the core material, the condensation reaction of urea and formaldehyde, the molecular weight of the urea-formaldehyde condensation product gradually increases, and the polymer is separated from the aqueous phase to become a coacervate phase; the wetting and wrapping process is that part of the coacervate phase is dispersed in the aqueous phase to form an emulsion, and part of it is wrapped on the surface of the core material droplets to form a liquid film. The coacervate phase wrapped on the surface of the core material droplets is further condensed, cross-linked, and solidified to form the microcapsule wall; the film layer solidification process is that the coacervate phase dispersed in the aqueous phase is cross-linked and solidified to form a colloidal system coexisting with the microcapsule.
[0051] The present invention also provides a method for preparing the self-healing ceramic coating described in the above technical solution, comprising the following steps: first mixing polydimethylsiloxane and xylene to obtain a first mixed liquid, and then second mixing the first mixed liquid with microcapsules to obtain the self-healing ceramic coating.
[0052] In the present invention, the mass ratio of the first mixed liquid to the microcapsules is preferably 100:15; the first mixing and the second mixing are preferably performed by ultrasound, and the ultrasound time is preferably 10 minutes.
[0053] The present invention also provides a method for preparing a self-repairing ceramic coating, comprising the following steps:
[0054] The self-repairing ceramic coating described in the above technical solution is applied to a metal surface, and the obtained prefabricated coating is laser cracked under a protective atmosphere to crack the polydimethylsiloxane in the self-repairing ceramic coating to form silicon-oxygen-carbon ceramics, thereby obtaining a self-repairing ceramic coating.
[0055] In the present invention, the metal is preferably an iron-based metal or a copper-based metal, and the iron-based metal preferably includes 45# steel.
[0056] In the present invention, the thickness of the pre-coating layer is preferably 0.2-0.4 mm, and specifically 0.3 mm. The present invention has no special requirements for the coating method, and the method commonly used by those skilled in the art can be used.
[0057] In the present invention, the protective atmosphere gas preferably includes argon gas, and the flow rate of the argon gas is preferably 350 to 500 mL / min.
[0058] In the present invention, the laser cracking is preferably performed by laser scanning in an argon atmosphere, and the parameters of the laser scanning include: fiber pulse laser, the wavelength is preferably 1064nm, the line width length is preferably 10-15mm, specifically 12mm, the power is preferably 100-400W, specifically 300W, the scanning speed is preferably 10-15mm / s, specifically 12mm / s, the number of scans is preferably 3-4 times, the overlap rate is preferably 5%, and the scanning path is preferably S-shaped. During the laser cracking process, the polydimethylsiloxane in the self-repairing ceramic coating forms a silicon oxygen carbon ceramic layer, and the reactions that occur are as follows:
[0059]
[0060] The laser cracking parameters described in the present invention can form a silicon oxygen carbon ceramic layer without causing ablation and cracking of the microcapsules and losing the self-repairing function.
[0061] In the present invention, the laser pyrolysis preferably further includes cooling. The present invention has no special requirements for the cooling method, such as natural cooling in the air for 5 minutes.
[0062] The present invention also provides a self-repairing ceramic coating obtained by the preparation method described in the above technical solution, comprising a silicon-oxygen-carbon ceramic layer and microcapsules dispersed in the silicon-oxygen-carbon ceramic layer.
[0063] In the present invention, the thickness of the self-repairing ceramic coating is preferably 100-300 μm, and specifically may be 150 μm.
[0064] In the present invention, the volume proportion of the microcapsules in the self-healing ceramic coating is preferably 10% to 20%.
[0065] When the surface of the projectile is scratched, the microcapsules rupture and the internal liquid overflows and spreads to the damaged area, playing a corrosion-resistant and protective role. The self-repairing ceramic coating of the present invention has excellent corrosion-resistant and wear-resistant secondary protective effects on the damaged area.
[0066] The present invention also provides the use of the self-repairing ceramic paint or self-repairing ceramic coating described in the above technical solution in the clamped annular surface of the projectile.
[0067] The present invention coats the clamped annular surface of the projectile instead of the entire projectile, thereby achieving long-term corrosion protection in both intact and damaged states, and can save costs.
[0068] In order to further illustrate the present invention, the self-healing ceramic coating, coating, preparation method and application thereof provided by the present invention are described in detail below in combination with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0069] Example 1
[0070] The method for preparing the corrosion-resistant and reinforced self-repairing coating for the clamped ring surface of the projectile comprises the following steps:
[0071] Step 1: Preparation of microcapsules. First, at room temperature, add 5.00g urea, 0.50g ammonium chloride, 0.50g resorcinol and 200mL deionized water to a 1000mL beaker and stir evenly. After fully dissolved, adjust the stirrer speed, slowly add 1525mL of core material (epoxy resin 711 and bisphenol A epoxy resin E-51, where the addition amount of 711 is 20% of the volume of E-51), and adjust the pH value to 3.3-3.7 with hydrochloric acid. After stabilization, add 12.67g of 37wt% formaldehyde aqueous solution, heat in a constant temperature water bath (50-60℃), react for 5h, and use a PHS-3B pH meter to monitor the pH value and maintain it at 3.3-3.7. After the reaction is completed, the reaction solution is cooled naturally, and then solid-liquid separation (suction filtration), ethyl acetate extraction, water washing, and drying are performed to prepare microcapsules with an average particle size of 90-140 μm and a wall thickness of 30-50 μm.
[0072] Step 2: Prepare a mixed solution. Weigh 60 g of polydimethylsiloxane and 40 g of xylene, first ultrasonically disperse the polydimethylsiloxane and xylene for 10 minutes, then add 15 g of the microcapsules prepared in step 1 into the mixed solution, and continue ultrasonically dispersing for 10 minutes to obtain a uniform dispersion.
[0073] Step 3: Prepare a pre-coating layer. Apply the dispersion obtained in step 2 to the surface of 45# steel by brushing to obtain a pre-coating layer with a smooth surface and a thickness of 0.3 mm ± 0.1 mm.
[0074] Step 4: Prepare a self-repairing ceramic layer. The prefabricated coating obtained in step 3 is placed in an insulated furnace, with argon as the protective gas and an argon flow rate of 500 mL / min, and then the prefabricated coating is scanned with a laser, wherein the laser scanning process parameters include: laser wavelength: 1064 nm, line width length: 12 mm, power: 300 W, scanning speed: 12 mm / s, scanning 3 times, overlap rate of 5%, and setting the scanning path to S-type.
[0075] Step 5: Obtaining a ceramic coating: After the prefabricated coating is laser scanned, it is naturally cooled in the air for 5 minutes, and the sample is taken out to obtain a SiOC (silicon oxycarbide) ceramic coating filled with microcapsules with a thickness of 150 μm.
[0076] Figure 1 Schematic diagram of the coating ring surface of the corrosion-resistant strengthening self-repairing coating on the clamped ring surface of the projectile in the embodiment;
[0077] Figure 2 This is a process flow chart of preparing polyurea formaldehyde coated epoxy resin core microcapsules by in-situ polymerization in the embodiment;
[0078] Figure 3 This is a process flow chart of preparing SiOC ceramic coating by laser pyrolysis microcapsule filling system in the example.
[0079] Figure 4 The following is a scanning electron microscope image of the polyurea formaldehyde coated epoxy resin core microcapsule prepared by in-situ polymerization in Example 1, wherein (a) is the overall image and (b) is the capsule shell of the broken capsule. As can be seen from (a), the surface of the synthesized microcapsule is rough and dense, and the polyurea formaldehyde nanoparticle sediment can be clearly observed. As can be seen from (b), the capsule shell consists of two parts, the inner wall is a smooth and dense structure, and the outer wall is formed by the accumulation of polyurea formaldehyde particles and is relatively loose. The capsule was fixed and cut open to observe the wall thickness, and it can be seen that the wall thickness of the microcapsule is relatively uniform, about 45μm.
[0080] Figure 5 This is a scanning electron microscope image of a microcapsule that was broken after the ceramic layer of the projectile was scratched. It can be clearly seen that the microcapsule broke during the crack propagation process, and it was found that the repair agent resin was left in the microcapsule shell, and the repair agent also remained in the "tail". From the picture, we can see the repair liquid flowing out from the inside of the shell, and the microcapsule shell pointed by the black arrow.
[0081] Figure 6 This is an electron microscope image of two microcapsules that were cracked after the elastomer ceramic layer was scratched. It can be clearly seen that the two cracked microcapsules are fused together by the repair liquid.
[0082] Comparative Example 1
[0083] The difference from Example 1 is step 4, and the remaining steps are the same as Example 1.
[0084] Step 4: Prepare a self-repairing ceramic layer. The prefabricated coating obtained in step 3 is placed in an insulated furnace, with argon as the protective gas and an argon flow rate of 500 mL / min, and then the prefabricated coating is scanned with a laser, wherein the process parameters of the laser scanning include: laser wavelength: 1064 nm, spot size: 12 mm, power: 400 W, scanning speed: 5 mm / s, scanning 3 times, overlap rate of 5%, and setting the scanning path to S-type.
[0085] Figure 7 This is an electron microscope image of the microcapsule-filled ceramic layer (microcapsule rupture) prepared by the laser cracking process of Comparative Example 1. The instantaneous high-temperature thermal ablation of the laser impact causes the microcapsule wall to completely shatter, the microcapsule wall in the ceramic matrix disappears, the wrapped repair resin flows out, and the microcapsule wall is completely shattered and loses its self-repairing function.
[0086] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A self-repairing ceramic coating, characterized in that: Includes polydimethylsiloxane, xylene and microcapsules; The capsule core of the microcapsule is epoxy resin, and the capsule wall is polyurea formaldehyde; the mass content of the microcapsules in the self-repairing ceramic coating is 10-20%; The mass ratio of the polydimethylsiloxane to xylene is 2-4:1-3.
2. The self-repairing ceramic coating according to claim 1, characterized in that: The average particle size of the microcapsule is 90-140 μm, and the thickness of the capsule wall is 30-50 μm.
3. The self-repairing ceramic coating according to claim 1 or 2, characterized in that: The epoxy resin includes epoxy resin 711 and bisphenol A epoxy resin E-51, and the volume ratio of the epoxy resin 711 to the bisphenol A epoxy resin E-51 is 1:4-6.
4. The self-repairing ceramic coating according to claim 1, characterized in that: The microcapsules are prepared by an in-situ polymerization method, which comprises the following steps: Mixing urea, ammonium chloride, resorcinol and water to obtain a mixed solution; The epoxy resin is added dropwise to the mixed solution, the pH value is adjusted to 3.3-3.7, and the mixed solution is mixed with formaldehyde aqueous solution to carry out in-situ polymerization reaction to obtain microcapsules.
5. The self-repairing ceramic coating according to claim 4, characterized in that: The temperature of the in-situ polymerization reaction is 50-60° C. and the time is 4-6 hours.
6. A method for preparing a self-repairing ceramic coating, characterized in that: The invention comprises the following preparation methods: The self-repairing ceramic coating according to any one of claims 1 to 5 is applied to a metal surface, and the obtained prefabricated coating is subjected to laser cracking under a protective atmosphere to crack the polydimethylsiloxane in the coating to form silicon-oxygen-carbon ceramics, thereby obtaining a self-repairing ceramic coating.
7. The preparation method according to claim 6, characterized in that: The protective atmosphere gas is argon gas, and the flow rate of the argon gas is 350-500 mL / min.
8. The preparation method according to claim 6 or 7, characterized in that: The parameters of the laser cracking include: fiber pulse laser, wavelength of 1064nm, line width of 10-15mm, power of 100-400W, scanning speed of 10-15mm / s, scanning times of 3-4 times, overlap rate of 5%, and S-shaped scanning path.
9. The self-repairing ceramic coating obtained by the preparation method according to any one of claims 6 to 8, characterized in that: The invention comprises a silicon oxycarbon ceramic layer and microcapsules dispersed in the silicon oxycarbon ceramic layer.
10. Use of the self-healing ceramic coating according to any one of claims 1 to 5 or the self-healing ceramic coating according to claim 9 in the clamped annular surface of a projectile.